Acute Acquired Comitant Esotropia in Adults: Is It Neurologic or Not? - Kadriye Erkan Turan; Tulay Kansu (Journal of Ophthalmology)
Objectives. Acute acquired comitant esotropia (AACE) can be a diagnostic challenge for ophthalmologists and neurologists because of its association with neurological pathologies. Our study describes a series of adult patients with AACE of undetermined etiology. Methods. Data on the clinical findings of patients presented with AACE of undetermined etiology with a minimum follow-up of 1 year were retrieved from the medical records and the results analyzed. Results. A series of 9 esotropia cases (age range: 20–43 years) was reviewed. All patients had full duction and versions, without an A-pattern or V-pattern. All patients had esotropia for distance and near. Neurological evaluation in all cases was normal. Among patients, 3 were treated with prisms, 4 were treated with strabismus surgery, and 1 was treated with botulinum toxin injections; 1 patient declined treatment. In treated patients posttreatment sensory testing indicated restoration of binocularity that remained stable throughout follow-up of 1–9 years. The patient that declined treatment had binocular function with base-out prisms. Conclusion. Acute onset esotropia may be seen without a neurological pathology in adults. Good motor and sensory outcomes can be achieved in these patients with AACE of undetermined etiology via surgical and nonsurgical methods.